2022
DOI: 10.7589/jwd-d-21-00029
|View full text |Cite
|
Sign up to set email alerts
|

Mountain Lions (Puma Concolor) Resist Long-Term Dietary Exposure to Chronic Wasting Disease

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…To date, CWD has largely failed to cause disease in these mice [ 98 , 99 , 100 , 101 , 102 , 103 ]; however, a recent study provides evidence that CWD can infect transgenic mice that express human PrP C , albeit with a low attack rate and at times post-infection that are at the end of the animal’s life span [ 104 ]. CWD can infect other sympatric species following direct inoculation of the brain (e.g., cattle, cats); however, these species do not develop disease following natural routes of infection [ 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 ]. Importantly, swine and sheep are an exception where ingestion or nasal exposure of CWD prions results in replication of CWD prions, but these animals do not develop clinical signs of disease [ 114 , 115 ].…”
Section: Interspecies Transmission Of Cwdmentioning
confidence: 99%
“…To date, CWD has largely failed to cause disease in these mice [ 98 , 99 , 100 , 101 , 102 , 103 ]; however, a recent study provides evidence that CWD can infect transgenic mice that express human PrP C , albeit with a low attack rate and at times post-infection that are at the end of the animal’s life span [ 104 ]. CWD can infect other sympatric species following direct inoculation of the brain (e.g., cattle, cats); however, these species do not develop disease following natural routes of infection [ 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 ]. Importantly, swine and sheep are an exception where ingestion or nasal exposure of CWD prions results in replication of CWD prions, but these animals do not develop clinical signs of disease [ 114 , 115 ].…”
Section: Interspecies Transmission Of Cwdmentioning
confidence: 99%
“…The infected cervids are more vulnerable to predation; thus, predators are more likely to be exposed to the prions by consuming the infected meat, possibly leading to a disturbance in the natural selection of species and ecosystem imbalance [ 11 , 12 ]. However, no research to date has indicated CWD transmission to predators such as the mountain lion ( Puma concolor ) [ 13 ]. CWD has also shown a zoonotic potential as experimental research suggested a transmission possibility to humanized mice, squirrels, and monkeys [ [14] , [15] , [16] ].…”
Section: Introductionmentioning
confidence: 99%